Vaccine prevention of meningococcal disease, coming soon? - Morley, S; Pollard, A (2001)
The past century has seen the use of a number of vaccines for prevention and control of meningococcal disease with varied success. The use of polysaccharide vaccines for the control of outbreaks of serogroup C infections in teenagers and young adults and epidemic serogroup A disease has been established for 30 years and an effective protein-polysaccharide conjugate vaccine against serogroup C was introduced into the UK infant immunisation schedule in 2000. The next generation of these glycoconjugate vaccines will be on the shelf soon, eventually offering the prospect of eradication of serogroups A, C, Y and W135 through routine infant immunisation. Despite these exciting prospects, serogroup B meningococci still account for a majority of infections in industrialised nations but development of safe, immunogenic and effective serogroup B meningococcal vaccines has been an elusive goal. Outer membrane vesicle vaccines for B disease are already used in some countries, and will likely be used more widely in the next few years, but efficacy for endemic disease in children has so far been disappointing. However, the innovations arising from the availability of the meningococcal genome sequence, public and scientific interest in the disease and recent pharmaceutical company investment in development of serogroup B vaccines may have started the countdown to the end of meningococcal infection in children.